2012
DOI: 10.1002/chem.201203144
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced CO2 Adsorption over Polymeric Amines Supported on Heteroatom‐Incorporated SBA‐15 Silica: Impact of Heteroatom Type and Loading on Sorbent Structure and Adsorption Performance

Abstract: Silica supported amine materials are promising compositions that can be used to effectively remove CO(2) from large stationary sources, such as flue gas generated from coal-fired power plants (ca. 10 % CO(2)) and potentially from ambient air (ca. 400 ppm CO(2)). The CO(2) adsorption characteristics of prototypical poly(ethyleneimine)-silica composite adsorbents can be significantly enhanced by altering the acid/base properties of the silica support by heteroatom incorporation into the silica matrix. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
113
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 119 publications
13
113
0
2
Order By: Relevance
“…Pluronic P123 block copolymer (EO 20 All SBA-15 materials were prepared according to previous reports [18,19,37,[49][50][51][52][53][54][55]. The details of the synthetic procedures are in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Pluronic P123 block copolymer (EO 20 All SBA-15 materials were prepared according to previous reports [18,19,37,[49][50][51][52][53][54][55]. The details of the synthetic procedures are in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…[10] Efforts have been made to improve on the traditional amine system by using ionic liquids, [11] as well as making solid supported amines. [12][13][14][15][16][17] However, there is no significant decrease in the desorption temperature of the CO 2 . We have recently reported that when polyethyleneimine (PEI, I) was covalently bonded to single-walled carbon nanotubes (SWNTs) the CO 2 uptake was enhanced as compared to the polymer itself.…”
Section: Introductionmentioning
confidence: 98%
“…Composite materials that combine the zeolitic microporosity with the mesoporosity in amorphous phase of M41S family have attracted special attention due to potential properties and applications in adsorption and catalysis [3]. These properties are not related to the mesoporous and zeolite individual phase characteristics, but with the final assembly and synergy that is consequently formed between the two structures [4].…”
Section: Introductionmentioning
confidence: 99%